Reliability of a 3-min all-out Arm Crank Ergometer Exercise Test - Flueck, J. L.; Lienert, M.; Schaufelberger, F.; Perret, C. (International Journal of Sports Medicine, 2015)
The 3-min all-out test is a well-established exercise test developed for cycling ergometry. However, no such test exists in arm cranking. Thus the aim of this study was to investigate the test-retest reliability of a 3-min all-out exercise test on an arm crank ergometer. 21 healthy participants (9 male and 12 female, age 34±11 years, body mass 69.6±11.1 kg and height 175.5±6.9 cm) twice performed a 3-min all-out exercise test on an arm crank ergometer separated by 7 days. Peak power (PP), mean power (MP), fatigue index (FI), time to peak (TTP) and total work (TW) were assessed to detect test-retest reliability. PP, MP, FI and TW showed an excellent intra-class correlation coefficient (ICC) ranging from 0.940 to 0.984. Only TTP showed very low reliability with an ICC of 0.379. The results from this test-retest analysis showed that all parameters except the TTP were highly reliable in a 3-min all-out exercise test on an arm crank ergometer in able-bodied participants.
Keywords: exercise performance; upper body exercise; study on reliability